Application of peptidases from Maclura pomifera fruit for the production of active biopeptides from whey protein - Bertucci, Juan Ignacio (2015)
A crude extract containing serine peptidases, was prepared from latex of Maclura pomifera fruits. Peptidases were isolated by precipitation with one volume of ethanol with a yield of 5.4 ± 0.4 Ucas per milligram of protein. This extract was used for hydrolysis of bovine whey proteins at 45 °C and pH 6.5. Proteolytic activity was 99% inactivated after 5 min of heat treatment (100 °C). Major whey proteins degradation profile was analysed by tricine SDS-PAGE. After 180 min of hydrolysis alpha-lactalbumin (α-LA) and beta-lactoglobulin (β-LG) were almost completely degraded. Hydrolysis degree was 31.3 ± 1.7% at 180 min of reaction and the peptides produced that were smaller than 3 kDa were analysed by reversed-phase high-performance liquid chromatography (RP-HPLC). Angiotensin-converting enzyme (ACE) inhibitory activity and antioxidant capacity were detected in the hydrolysates and IC50 values for 180 min of hydrolysis were 0.53 ± 0.02 and 4.44 ± 0.44 mg/ml, respectively. One peptide sequence deduced from peptide masses in the 180 min filtered hydrolysate, coincided with an ACE-inhibitory peptide reported by other author. The results support the conclusion that, by the presence of ACE-inhibitory and antioxidant peptides, it would be possible to use these whey protein hydrolysates for functional food manufacturing.